Spontaneous Resolution of Congenital Dural Venous Sinus Ectasia Associated With Polymicrogyria-Case Report - Zuzanna Kozłowska; Paulina Komasińska; Barbara Steinborn; Kinga Toboła-Wróbel; Marek Pietryga; Marta Szymankiewicz-Breborowicz; Tomasz Szczapa; Monika Bekiesińska-Figatowska (Frontiers Media S.A., 2022)
Dural venous sinus ectasia belongs to a rare group of venous sinus malformations of unknown origin and uncertain prognosis. We report the first patient with idiopathic congenital ectasia of the confluence of sinuses with thrombosis associated with bilateral polymicrogyria. It may highlight the causative relation between ischemia within the central nervous system due to torcular herophili ectasia with thrombosis in early pregnancy and the development of cortical malformations in neonates. We also highlight the role of MR neuroimaging in the diagnosis of these entities.